In the triangle of civil society, politics, and economy: positioning magazines of nonprofit organizations - Hoffmann, Jochen (Springer, 2011)
Nonprofit organizations, though rooted in civil society and primarily committed to value rationality, must work legitimately to influence political and economic systems. To a certain degree, therefore, they must adapt to the purposive logic of power and money. This study analyzes the way in which nonprofit organizational communications respond to such tensions, using a nationwide survey of editors-in-chief responsible for magazines issued by nonprofit organizations in Switzerland as the empirical basis. These magazines often function as steering tools targeted toward members, following the logic of power and there is less danger of them being ‘‘colonized’’ by economic logic. The results indicate that large organizations that rely on paid staff tend to cut their ties with civil society and the ‘‘lifeworlds’’ of their members.